Development and validation of nomogram including high altitude as a risk factor for COPD: A cross-sectional study based on Gansu population - Lin, Ao; Mao, Chun; Rao, Boqi; Zhao, Hongjun; Wang, Yunchao; Yang, Guokang; Lei, Haisheng; Xie, Chenli; Huang, Dongsheng; Deng, Yibin; Zhang, Xuhui; Wang, Xinhua; et al. (Frontiers in Public Health, 2023)
Background Chronic Obstructive Pulmonary Disease (COPD) is a common and harmful disease that requires an effective tool to early screen high-risk individuals. Gansu has unique environments and customs, leading to the different prevalence and etiology of COPD from other regions. The association between altitude and COPD once attracted epidemiologists’ attention. However, the prevalence in Gansu and the role of altitude are still unclarified. Methods In Gansu, a multistage stratified cluster sampling procedure was utilized to select a representative sample aged 40 years or older. The questionnaire and spirometry examination were implemented to collect participants’ information. The diagnosis and assessment of COPD were identified by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criterion, while post-bronchodilator FEV1/FVC